1968
DOI: 10.1177/001440296803400503
|View full text |Cite
|
Sign up to set email alerts
|

The Needs and Problems of Socially Disadvantaged Children as Perceived by Students and Teachers

Abstract: It was hypothesized in this study that there would be significant differences between perceptions of socially disadvantaged and other student and teacher groups on each subtest of the SRA Junior Inventory. Although the hypothesis was rejected, it was found that teachers have a better understanding of the needs and problems of disadvantaged youth than might be expected. Teachers, however, differed markedly with students by suggesting that the home rather than the school was the source of student frustration. Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1968
1968
1970
1970

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This is particularly critical with lower class children. Howard (1968) found that public school teachers in lower socioeconomic urban areas were rejecting in their attitudes toward lower class children. His evidence also indicated that teachers do not appreciate the problems which are most important to lower class children.…”
Section: The Classroom Teacher As Mental Health Workermentioning
confidence: 99%
“…This is particularly critical with lower class children. Howard (1968) found that public school teachers in lower socioeconomic urban areas were rejecting in their attitudes toward lower class children. His evidence also indicated that teachers do not appreciate the problems which are most important to lower class children.…”
Section: The Classroom Teacher As Mental Health Workermentioning
confidence: 99%